Debra Seenoi's transcript, Kenya, June 13, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
"To have access to the research data file, please contact: Joana Roque de Pinho: roquedepinho.joana@gmail.com"
Keywords: Arid regions; Maasai (African people); Tourism; East Africa; Kenya; Conflict; COVID-19 Pandemic